Effect of rosuvastatin on risk markers for venous thromboembolism in cancer. (29th April 2018) - Ades, S.; Douce, D.; Holmes, C. E.; Cory, S.; Prior, S.; Butenas, S.; Callas, P.; Cushman, M.
Abstract : Essentials Statins lower venous thromboembolism risk in general but have not been studied in cancer patients. We completed a randomized trial of rosuvastatin vs. placebo among cancer patients on chemotherapy. Rosuvastatin did not significantly lower prothrombotic biomarkers including D‐dimer. The role of statins in venous thrombosis prevention in cancer patients remains unknown. Summary: Background: Statin therapy is associated with lower risk of venous thromboembolism (VTE) but has not been prospectively evaluated in patients with advanced cancer. Objectives: We determined if statin administration in this high‐risk population reduces the risk of VTE, based on established and emerging biomarkers. Patients/Methods: This double‐blind, crossover, randomized controlled trial among patients with advanced cancer receiving systemic therapy allocated participants to rosuvastatin 20 mg daily or placebo for 3–4 weeks prior to crossover to the alternative therapy, with a 3–5‐week washout. D‐dimer, C‐reactive protein (CRP), soluble (s)P‐selectin, factor VIII (FVIII), thrombin generation and exploratory biomarkers focusing on endogenous thrombin potential, including tissue factor (TF), activated factor IX (FIXa) and activated factor XI (FXIa), were measured at the start and end of both treatment periods. The primary outcome was change in D‐dimer with rosuvastatin compared with placebo. Results: Of 38 enrolled participants, 24 (63%) completed the study. Rosuvastatin did not cause statistically significant changes in D‐dimer levels or any other biomarker. CRP levels decreased by 40%; 4.3 mg L −1 (95% confidence interval, −11.0 to +2.5 mg L −1 ) compared with placebo. In post‐hoc analysis, participants who received rosuvastatin initially during their first line of treatment had a 13% decrease in D‐dimer. Circulating TF, FIXa and FXIa were detected in 26%, 68% and 71% of cancer patients despite not being found in healthy individuals. Conclusions: Rosuvastatin did not cause favorable changes in biomarkers of VTE risk in advanced cancer patients receiving chemotherapy. The role of statin therapy as thromboprophylaxis in the cancer population remains uncertain.